Effects of trigger-day progesterone in c-IVF/ICSI cycles on blastocyst culture outcomes - Sun, Yating; Wang, Jia; Zhang, Luyun; Chang, Yanjun; Zhu, Aizhen (Frontiers in Endocrinology, 2025)
ObjectiveTo assess whether trigger-day progesterone (P) levels in conventional in vitro fertilization (c-IVF)/intracytoplasmic sperm injection (ICSI) cycles are associated with blastocyst culture outcomes.MethodsIn this retrospective analysis, 747 eligible patients (747 cycles) who adopted the gonadotropin-releasing hormone (GnRH) antagonist protocol and underwent c-IVF/ICSI between January 2021 to June 2024 were recruited. The P cutoff values were 1.0 and 1.5 ng/ml when trigger-day serum P was measured, and 4177 day3 (D3) embryos for blastocyst culture were grouped according to trigger-day P levels. Furthermore, the effects of trigger-day P on blastocyst culture outcomes were evaluated.ResultsIn total, 747 cycles, 4177 D3 embryos for blastocyst culture were analyzed. After adjustments, multivariate logistic regression analysis revealed that compared with those in the normal level group, available blastocyst rate (adjusted OR, 0.780; 95% CI, 0.645-0.942; P=0.010) and D5 available blastocyst rate (adjusted OR, 0.736; 95% CI, 0.604-0.898; P=0.003) in the high level group were significantly reduced. Subgroup analysis showed that when female age was less than 35 years old, compared with that (36.30%) in the normal level group, the D5 available blastocyst rate (36.92%, adjusted OR, 0.744; 95% CI, 0.602-0.920; P=0.006) in the high level group was significantly reduced. In ICSI cycles, compared with that (28.69%) in the normal level group, the D5 available blastocyst rate (19.13%, adjusted OR, 0.369; 95% CI, 0.194-0.703; P=0.002) in the high level group was significantly decreased.Conclusion(s)This study demonstrated that in the c-IVF/ICSI population, the trigger-day slightly elevated P (1.0-1.5ng/ml) was not related to blastocyst culture outcomes, while the trigger-day elevated P (>1.5ng/ml) was an important factor affecting D5 available blastocyst rate, especially when the woman was younger than 35 years old or insemination type was ICSI.